Data dissemination Issue and protocol in WSN a survey (International Journal of Engineering and Computer Science, 2017)
There are a few special features of WSN like restricted battery life, bound computing  routing capabilities etc. for the reason that of these particular features of wireless sensor networks, routing algorithms of mobile ad-hoc networks are not appropriate. The current data dissemination system is not energy-efficient for this problem several algorithms and routing protocols are used over the past decade. There are many protocols are used to determine the best way for energy utilization in wireless sensor networks. This paper tries to study most of the data dissemination protocol used in WSN. Finally most of the protocols will categorized and analyzed. We try to design an algorithm which keeps in account the battery life of nodes and uses more and more nodes with better battery life.